(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Depleting oil reserves and environmental concerns on emission have heightened the search for alternative energy sources and efficient electrochemical energy systems through renewable energy sources. Technological advancements in the field of automation, robotics, communication, nanotechnology, electrification and hybridization of vehicles as well as the push for renewable energy sources have broadened the scope of opportunities for Electrochemical Energy Storage Systems (ESS). These new technologies place a growing demand on compact, safe and higher capacity batteries to enable functionality. Battery technology for different needs and application have become an indispensable aspect of sustainable development in the quest for renewable energy and global sustainable carbon emission reduction. This paper briefly looks at the integrated nature of batteries to human day to day activities, the current state and impact of battery technology, future of energy storage systems and an analysis of battery storage systems for sustainable industrialization.